ISA-USB interface module - De Luna, Jose Rey C. (1997)
This project aims to develop an Industry Standard Architecture Bus (ISA Bus) in Universal Serial Bus (USB) interface module. The ISA Bus is the conglomeration of signals occurring in 8086 and 80x86 microprocessor based personal computers (PCs), allowing the connection of external devices to the PC. It is a parallel bus and thus, would need serial adapter cards to interface with serial devices. One of the biggest problems with PCs today, however, is the lack of enough serial adapter cards and facilities to accommodate them, especially now that there is an increasing number of serial devices brought about by the merging of the computer and communications industries. Indeed there is a demand for more serial ports to accommodate devices such as modems, fax machines, voice and video equipment, and other miscellaneous equipment not related to communications. The Universal Serial Bus n a new development in the computer industry n answers this need. It is a small group of signals which allows serial devices to interface to the computer. A USB could handle up to 127 serial devices from a single port, thus dramatically increasing the number of devices a single PC could control, in turn increasing that PCs capability. The development of a USB is done using Electronic Design Automation (EDA) tools. These include VHDL (Very High Speed Integrated Circuit Description language) for design at a high level of abstraction, gate-level synthesis tools, and a Field Programmable Gate Array (FPGA) implementation.
Thesis (B.S. E.E.)--University of the Philippines Diliman.
Keywords: USB (Computer bus); Computer interfaces; Computer architecture; Industry Standard Architecture Bus; Universal Serial Bus